2019
DOI: 10.14814/phy2.14194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of all‐out sprint interval training under hyperoxia on exercise performance

Abstract: All‐out sprint interval training (SIT) is speculated to be an effective and time‐efficient training regimen to improve the performance of aerobic and anaerobic exercises. SIT under hypoxia causes greater improvements in anaerobic exercise performance compared with that under normoxia. The change in oxygen concentration may affect SIT‐induced performance adaptations. In this study, we aimed to investigate the effects of all‐out SIT under hyperoxia on the performance of aerobic and anaerobic exercises. Eighteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Thus, in addition to increasing a session TL per se , hyperoxia may also be an effective environmental stress for inducing peripheral adaptations by imposing repeated muscle oxygenation fluxes. For instance, Kon et al ( 2019 ) reported an improvement in lactate curve at submaximal exercise after 3 weeks of sprint-interval (30-s sprint) training with 60% O 2 in college athletes, which could be related to an improvement in mitochondrial oxidative capacity. On the other hand, 6-week interval training between 80 and 100% of maximal aerobic power with 30% O 2 in trained cyclists did not result in any improvement in mitochondrial phosphorylation capacity nor markers of mitochondrial content (Cardinale et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to increasing a session TL per se , hyperoxia may also be an effective environmental stress for inducing peripheral adaptations by imposing repeated muscle oxygenation fluxes. For instance, Kon et al ( 2019 ) reported an improvement in lactate curve at submaximal exercise after 3 weeks of sprint-interval (30-s sprint) training with 60% O 2 in college athletes, which could be related to an improvement in mitochondrial oxidative capacity. On the other hand, 6-week interval training between 80 and 100% of maximal aerobic power with 30% O 2 in trained cyclists did not result in any improvement in mitochondrial phosphorylation capacity nor markers of mitochondrial content (Cardinale et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%